The Influence of Social Capital, Social Institutions and Local Potential Moderated By Entrepreneurial Spirit on The Success of The Business - Winarno, Agung; Agustina, Yuli; Ichwanto, M. Aris; Churiyah, Madziatul (Economics and Business Journal (ECBIS), 2024)
This study intends to investigate the impact of social capital, social institutions, and local potential on the success of KUBE start-ups, as regulated by an entrepreneurial mindset. This study's population consists of VCO business players who belong to joint business organizations. The sample consisted of 200 respondents chosen using the approach of purposive sampling. The data utilized are both original data collected from respondents via questionnaires and secondary data. This study uses Structural Equation Modeling (SEM) with the SmartPLS application to handle data. According to the findings of this study, Social Capital and Social Institutions have little effect on the success of KUBE Start Up. Meanwhile, Local Potential and Entrepreneurial Spirit have a substantial beneficial impact on KUBE Start Up's success. Entrepreneur Spirit does not mitigate the influence of Social Capital, Social Institutions, and Local Potential on KUBE Startup's success.